Dimensi Ekonomi Produktif dalam Regulasi Wakaf di Indonesia - Hadi, Solikhul (TAWAZUN: Journal of Sharia Economic Law, 2020)
Waqf is a form of worship in Islam which has productive economic value. And Law no. 41 of 2004 concerning Waqf has opportunities for economic development for the benefit of social welfare. For this reason, it is necessary to have a study that analyzes the Waqf Law from a productive economy perspective. In this study, using content analysis method, which is an in-depth discussion of the content of written or printed information. In this case Law No.41 of 2014 concerning Waqf seeks to be coherent with productive economic theory. And the theory used as an analysis tool is the productive economic theory of Qutub Abdul Salam, in terms of the dimensions of productive economic goals and the main factors needed. Thus, this research actually aims to find the coherence of the articles in the Waqf Law with the Productive Economic Theory developed by Qutub Abdul Salam. From the results of data collection and analysis, it can be concluded that the Waqf Law is kohern with productive economic theory. The purpose of productive economic activities is to increase the benefit that can be realized in various forms, including: Meeting human needs at a moderate level, finding community needs and their fulfillment, providing supplies of goods / services in the future and fulfilling the means for social activities and worship of Allah. Among the articles in the Waqf Law which are coherent with productive economic objectives is article 5 of the Waqf Law, which explains that waqf functions to realize the economic potential and benefits of waqf assets for the benefit of worship and to promote public welfare. In productive economic theory, the productivity factors of a business include four things: natural resources, managers / workers, skills and capital. The natural resource factor as one of the factors in the development of the productive economy is coherent with the Waqf Law, namely waqf objects in the form of land, buildings or other immovable objects. The productivity factor in the form of managers or workers managing and carrying out waqf assets is nazir which includes; individual, organization, or legal entity. Skill is a very important productivity factor in managing waqf assets. Nazir as the manager of the waqf will receive guidance from the Minister of Religion and the Indonesian Waqf Board (BWI) both in terms of skills and managerial. And the capital factor in the context of the management of waqf assets is the object of waqf. In the Law on Waqf the objects of waqf include movable and immovable objects. With the issuance of the Waqf Law No. 41 of 2014, immovable objects have become important assets in the development of productive waqf. Movable property that cannot be used up due to consumption includes: money, precious metals, securities, vehicles, intellectual property rights, lease rights and other movable objects in accordance with the provisions of sharia and applicable laws and regulations.